PENGARUH BIAYA PRODUKSI DAN BIAYA OPERASIONAL TERHADAP LABA BERSIH: (STUDI KASUS PERUSAHAAN FARMASI YANG TERDAFTAR DI BEI PADA TAHUN 2018-2022) - Maya Refalina, Novera Martilova (CV. ADIBA AISHA AMIRA, 2024)
The research is motivated by the influence of production costs and operational costs on net profit. This research aims to find out and analyze how much influence production costs and operational costs have on the net profit of case studies of pharmaceutical companies listed on the IDX in 2018-2022). The research is motivated by the Impact of Creation Fees and Operational Fees on Net Profit. This research intends to identify and analyze how much the Impact of Creation Fees and Operational Fees on Net Profit Research on Pharmaceutical Industry Problems Listed on the IDX in 2018-2022). The type of research used is a quantitative method and the type of information is inferior information. The method of collecting illustrations in this research is a purposive sampling method with a total of 11 industries. The information analysis method uses descriptive statistical experiments, classical assumption experiments, namely, normality experiments, multicollinearity experiments, heteroscedasticity experiments, multiple linear regression analysis, autocorrelation experiments, experiments (R2), and hypothesis experiments. The results of this research partially prove that in elastic production fees have an insignificant impact on net profit as evidenced by the results of the experiment t count ? t table 1. 235 ? 1. 31253 with significant figures 0.227? 0.05. Operational costs have an important effect on net profit as evidenced by the results of t count? t table 3.581?1.31253 with significant figures 0.001? 0.05. Creation costs and operational costs simultaneously have an important effect on net profit as evidenced by f count? f table 8.230?3.35 with significant figures 0.002? 0.05. In the Experiment (R2) the elasticity of Creation Costs and Operational Costs can affect Net Profit by 37.9% while the excess of 62.1% is influenced by other aspects that are not studied